Zniszczenia wojenne i odbudowa Skwierzyny w latach 1945-1949 = The destruction of war and the restoration of city Skwierzyna in 1945-1949 - Urbanek, Grzegorz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Skwierzyna was one of the most damaged cities in the time of world war II and the presence of Red Army troops (especially soviet war headquarters). The article shows scale of destruction of buildings, municipal objects, communication infrastructure and industry.
Keywords: Skwierzyna; II (druga) wojna światowa; radziecka komendantura wojenna; odbudowa powojenna; world war II; Soviet war command; restoration of the city